Tunable Electrical Performance of Few‐Layered Black Phosphorus by Strain. Issue 38 (22nd August 2016) - Wu, Hongrong; Liu, Xiaofei; Yin, Jun; Zhou, Jianxin; Guo, Wanlin
Abstract : Strain engineering shows promising applications in low‐dimensional materials. It is demonstrated that the bandgap of few‐layered black phosphorus can be effectively reduced by out‐of‐plane compressive strain, resulting in a significant modulation of the vertical electrical performance of black phosphorus and even inducing a nonlinear current–voltage curve to linear current–voltage curve transition.